The witch's daughter - Brackston, Paula (Thomas Dunne Books, 2011)
Witnessing the death of her witch mother in the spring of 1628, Bess Hawksmith turns to secluded warlock Gideon Masters for protection and learns formidable powers, including immortality, skills she begins teaching to a new apprentice centuries later.